Emotion and the seduction of the senses, Baroque to neo-Baroque - Beaven, Lisa; Ndalianis, Angela, 1960- (Studies in medieval and early modern culture ;, 2018)
Emotion and the Seduction of the Senses, Baroque to Neo-Baroque examines the relationship between the cultural productions of the baroque in the seventeenth century and the neo-baroque in our contemporary world. It asks the question: 'Is the baroque a recurring phenomenon that has returned in aspects of contemporary global culture, or is it something specific to the early modern period?' It argues one of the common and central features of both styles is their appeal to emotion. This volume illuminates how, rather than providing rationally ordered visual realms, both the baroque and the neo-baroque construct complex performative spaces whose spectacle seeks to embrace, immerse and seduce the senses and solicit the emotions of the beholder